TQM in Roads and Highways Department; Evaluate an approach-how it improves the performance of supply chain to its organization - Barua, Ranapriya (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2020.